2015
DOI: 10.1159/000430818
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Gonadotropin-Releasing Hormone Neurons of Male and Metestrous Female Mice

Abstract: Background: Gonadotropin-releasing hormone (GnRH) neurons play a pivotal role in the regulation of the hypothalamic-pituitary gonadal axis in a sex-specific manner. We hypothesized that the differences seen in reproductive functions of males and females are associated with a sexually dimorphic gene expression profile of GnRH neurons. Methods and Results: We compared the transcriptome of GnRH neurons obtained from intact metestrous female and male GnRH-green fluorescent protein transgenic mice. About 1,500 indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 111 publications
0
15
0
Order By: Relevance
“…In our present study, the mRNA content of the individual GnRH neurons of male mice used in PCR experiments was also harvested using the patch clamp pipette, as described earlier (Farkas et al, 2013; Vastagh et al, 2015) with slight modification. Patch pipettes were pulled from capillaries sterilized at 180°C for 6 h and filled with autoclaved intracellular pipette solution containing (in mM) HEPES 10, K-gluconate 130, KCl 10, NaCl 10, EGTA 1 and MgCl 2 0.1 (pH 7.3 with KOH, osmolarity adjusted to 300 mOsm with D-sorbitol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our present study, the mRNA content of the individual GnRH neurons of male mice used in PCR experiments was also harvested using the patch clamp pipette, as described earlier (Farkas et al, 2013; Vastagh et al, 2015) with slight modification. Patch pipettes were pulled from capillaries sterilized at 180°C for 6 h and filled with autoclaved intracellular pipette solution containing (in mM) HEPES 10, K-gluconate 130, KCl 10, NaCl 10, EGTA 1 and MgCl 2 0.1 (pH 7.3 with KOH, osmolarity adjusted to 300 mOsm with D-sorbitol).…”
Section: Methodsmentioning
confidence: 99%
“…The resistance of the patch electrodes was 2–3 MΩ. The RNA samples were collected from GnRH-GFP neurons of acute brain slices kept in oxygenated aCSF at 33°C (Farkas et al, 2013; Vastagh et al, 2015) using extra care to avoid any glial RNA contamination with the protocol suggested by Fuzik et al (2016). The collected cytoplasm was reverse transcribed directly in 20 μl reactions using the ViLO SuperScript III cDNA reverse transcription (RT) kit (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Brain fixation, preparation of sections for the subsequent laser capture microdissection (LCM) and microarray profiling were performed as reported elsewhere (Khodosevich et al, 2007 ; Vastagh et al, 2015 ). Briefly, metestrous ( n = 6) and proestrous female ( n = 6) mice were deeply anesthetized and perfused transcardially with 80 ml 0.5% paraformaldehyde followed by 20% sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…GABA- and glutamate-driven events of neurotransmission onto GnRH neurons have been the most comprehensively studied regulatory mechanisms of these neurosecretory cells (Christian and Moenter, 2010; Iremonger et al, 2010; Moenter, 2010; Penatti et al, 2010; Liu and Herbison, 2011; Taylor-Burds et al, 2015). A wide repertoire of GABA, glutamate and DA receptors characterizes the GnRH neurons (Todman et al, 2005; Vastagh et al, 2015, 2016), as a prerequisite of their control by neurotransmitters. The upregulation of solute carrier family 17, member 1 gene ( Slc17a6 ) that codes for vesicular glutamate transporter 2 (VGLUT2) indicates the probability of enhanced packaging of glutamate into synaptic vesicles at the level of axon terminals in proestrus.…”
Section: Discussionmentioning
confidence: 99%